2022
DOI: 10.1111/dar.13481
|View full text |Cite
|
Sign up to set email alerts
|

‘Even though you hate everything that's going on, you know they are safer at home’: The role of Aboriginal and Torres Strait Islander families in methamphetamine use harm reduction and their own support needs

Abstract: Introduction First Nations people who use methamphetamine are overrepresented in regional and remote Australia and more likely to turn to family for support. This can place strain on families. The support needs of family members of individuals using methamphetamine are poorly understood. Methods We conducted 19 focus groups and seven interviews with mostly First Nations community, family members and service providers. In total, 147 participants across six sites participated as part of a larger study investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Such assertions also hold beyond the Canadian context. Community-engaged harm reduction research emerging from Australia has shown the limitations of biomedical research approaches in work with Indigenous peoples living in smaller/rural communities, showing the strengths of communities and demonstrating how cultural safety and connection are key to empowering and supporting the well-being of Indigenous PWLLE dealing with mental health and addictions challenges [31,32].…”
Section: Also Think About Ways To Remove That Line Between the Resear...mentioning
confidence: 99%
“…Such assertions also hold beyond the Canadian context. Community-engaged harm reduction research emerging from Australia has shown the limitations of biomedical research approaches in work with Indigenous peoples living in smaller/rural communities, showing the strengths of communities and demonstrating how cultural safety and connection are key to empowering and supporting the well-being of Indigenous PWLLE dealing with mental health and addictions challenges [31,32].…”
Section: Also Think About Ways To Remove That Line Between the Resear...mentioning
confidence: 99%
“…Aboriginal and Torres Strait Islander people who have recently used methamphetamine reported significantly higher rates of racial discrimination, excessive grief, perceived social isolation and complex trauma than their non-Indigenous counterparts. [1,9,10] Key protective factors for Aboriginal and Torres Strait Islander participants included connection to culture and contact with…”
Section: Original Manuscriptmentioning
confidence: 99%
“…The results indicate helpline staff require evidence-based information, including brief interventions and other health promotion advice, on novel psychoactive substances and other substances for families, friends and treatment seekers. There is limited evidence on the impact of methamphetamine use on families, friends and concerned others [33,34], however qualitative studies on general AOD use highlight the feeling of helplessness and isolation experienced by caregivers and concerned others [35][36][37]. This may explain the pressure reported by some AOD helpline counsellors to find solutions for the caller, further compounded by the relative paucity of evidence-based interventions for the management of MED.…”
Section: Caller Groupsmentioning
confidence: 99%